A prospective observational comparative study on fetomaternal outcome and complications in obstetric patients with sickle cell disease or trait - Deshpande, Bhakti; Katariya, Aakanksha; Madhanure, Vanamala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Sickle cell disease (SCD) and sickle cell trait (SCT) are associated with increased fetomaternal morbidity and mortality, particularly in endemic regions like central India. Despite improved obstetric care, adverse outcomes persist, especially in endemic regions of central India. Methods: This prospective observational comparative study was conducted at the department of obstetrics and gynaecology, IGGMC and Mayo Hospital, Nagpur, from January 2023 to July 2024. A total of 190 pregnant women (95 with SCD/SCT and 95 controls with normal haemoglobin) were enrolled. Maternal and fetal outcomes were assessed and compared. Statistical analysis included Chi-square test and student’s t-test, with p<0.05 considered significant. Results: Women with SCD had significantly higher rates of preeclampsia, severe anemia, and sickle cell crises compared with controls. Fetal outcomes such as intrauterine growth restriction, low birth weight, and preterm delivery were also significantly more frequent in the study group (p<0.05). Cesarean delivery and blood transfusion requirements were higher in SCD cases. Conclusions: SCD and SCT adversely affect pregnancy outcomes, underscoring the need for multidisciplinary antenatal care, universal screening for sickle cell disease and delivery at tertiary care centres in endemic regions.